Sulfur-containing heterocyclic compounds with potential antidiabetic activity - E. A. Savateeva; V. V. Emelyanov; A. V. Musalnikova; L. P. Sidorova; N. E. Maksimova; N. N. Machulskaya; V. A. Chereshnev (Chimica Techno Acta)
The essential link in the pathogenesis of diabetes mellitus and its complications is a non-enzymatic glycosylation of proteins. However, modern endocrinology lacks of clinically effective pharmaceuticals for its correction. The screening of 23 derivatives of 1,3,4-thiadiazine the ability to inhibit the reaction of non-enzymatic glycosylation of proteins in vitro was held, and 11 the most active compounds of them were selected, also the relationship «structure – activity» was investigated. An essential part of the pathogenesis of diabetes mellitus and its complications is non-enzymatic glycosylation of proteins. However, modern endocrinology lacks clinically effective medicines for its correction.